An ecofriendly procedure to extract isoflavones from soybean seeds. (1st January 2018) - Lante, Anna; Barion, Giuseppe; Zannoni, Stefania; Pastore, Maria Rita; Tinello, Federica; Dal Cortivo, Cristian; Vamerali, Teofilo; Mosca, Giuliano
Abstract: A novel procedure for isoflavones extraction from soybean seeds using the "green solvent" water was set-up for its future industrial up-scaling. The optimized processing flow-scheme proposed here consists of a 1:5 flour weight-to-water volume ratio mixed by vertical stirrers for 6 min at 40 °C, with a final 12000-rpm centrifugation, and subsequent lyophilization to ensure stability and easy dosage of the extracts. Results showed that preliminary UV-C light flour irradiation for at least 1 h can improve isoflavones extraction and reduce anti-nutritional factors. Principal component analysis (PCA) and discriminant factorial analysis (DFA) highlighted specific operational conditions, such as extraction volume and time, UV time exposure, and centrifugation speed, for preferential extraction of specific isoflavones. The extraction efficiency varied according to variety choice within a range of 40–73%, possibly due to the relative abundance of the most water-soluble malonyl forms of isoflavones. As the extracts showed promising high stability under freezing and lyophilization conditions, it is concluded that, this ecofriendly extraction approach with can be successfully scalable, helping to save time and energy and obviating at disposal problems in the soy nutraceutical chain. Graphical abstract: Image 1 Highlights: The procedure meet the needs for ecofriendly extraction of soy isoflavones. Only water has been used as solvent. The isoflavones extracts showed a promising high stability. This approach can be successfully scalable.